Legal review of unaccompanied foreign minors in the European area. Analysis of the situation in Spain - Vicente Lorca, Alfonso (EUNOMÍA. Revista en Cultura de la Legalidad, 2022)
The issue of unaccompanied minors is a controversial matter in many territories in Europe. Due to this, coordination between all existing administrations is necessary to ensure compliance with the law and protect the human rights of children and adolescents who, due to different circumstances, find themselves in a situation of helplessness. For this reason, despite everything that has been advanced, legislation must continue to be adjusted to meet the needs of today, since the migratory phenomenon of minors is more and more frequent.